Fenomena “Jasa Penulis Online” dan Diferensiasi Sistem Komunikasi dalam Menjalankan Website di Indonesia - Khairul Arief Rahman (Jurnal Kopis: Kajian Penelitian dan Pemikiran Komunikasi Penyiaran Islam, 2022)
This paper will be explain the differentiation of communication system in running website industry in Indonesia. Problems regarding abour regulation on ITE Law which is still dwelling on content, of courses also sees complexity of the website industry in Indonesia itself. However, this is problematic when content creator judge or defined as productive people in communicate via social media and others. Meanwhile, the owner of website see the rise of “Online Writer Services” (JPO) as benefit to expand their business. The main problem is automatically leads to communication between website’s owner and JPO which can have impact on the content. This happens as shaped of system implementation to deal with complexity on the distribution and production of content. This paper is expected able to describe the differentiation of communication system in running website industry in Indonesia along with the advantage and the disadvantage of the quality of content that created by system and infrastructure. The method uses in this paper is literature studies and concepts regarding system differentiation.